Answer:
[tex] X \leq 3Y[/tex]
And we can rewrite this expression like this, subtracting 3Y from both sides of the last inequality:
[tex] X-3Y \leq 3Y-3Y[/tex]
And we got:
[tex] X -3Y \leq 0 [/tex]
And for this case the best answer would be:
b. X - 3Y≤ 0
Explanation:
For this case we need the following condition: "the quantity of X must be at most three times as large as the quantity of Y."
And we can convert this into a mathematical formula like this:
[tex] X \leq 3Y[/tex]
And we can rewrite this expression like this, subtracting 3Y from both sides of the last inequality:
[tex] X-3Y \leq 3Y-3Y[/tex]
And we got:
[tex] X -3Y \leq 0 [/tex]
And for this case the best answer would be:
b. X - 3Y≤ 0